Dietary Postbiotics Reduced Cytotoxicity and IL-1 Cytokine Release Induced by Crystalline Silica in Lipopolysaccharide-Primed Macrophages. (29th May 2020) - Du, Xue; Rodriguez, Jessica; Wierenga, Kathryn; Gavrilin, Mikhail; Holian, Andrij; Pestka, James; Wee, Josephine
Abstract: Objectives: Inhalation of crystalline silica (cSiO2) has been linked to the pathogenesis of human autoimmunity such as systemic lupus erythematosus. Alveolar macrophages (MΦ) are a major site of inflammasome activated release of pro-inflammatory cytokines, thus plays a vital role in the onset and progression of lupus. Diet supplemented with probiotics have been shown to decrease disease severity. The model used was the murine macrophage RAW 264.7 cell line (WT) and RAW 264.7 stably transfected with the inflammasome adapter protein ASC (RAW-ASC) as WT lacks a functional inflammasome. cSiO2 elicits robust inflammasome activation and IL-1β release in lipopolysaccharide (LPS)-primed RAW-ASC cells. We hypothesize that probiotic-associated cell-free fraction (postbiotics) could decrease cSiO2-induced cytotoxicity in MΦ and suppress pro-inflammatory IL-1 cytokines release. Methods: Lactobacillus rhamnosus (LGG), L. reuteri (REU), and Bifidobacterium lactis (BB12) were grown in de Man, Rogosa and Sharpe (MRS) broth. Postbiotics were collected and filtered between OD 1.0–3.0. RAW-ASC and WT cells were primed with LPS, stimulated with cSiO2 and treated with postbiotics or MRS control. Cytotoxicity and IL-1 cytokine release was measured by an Lactate dehydrogenase (LDH) assay and ELISA, respectively. Results: Postbiotics obtained at OD 3.0 exhibited greatest protective effect on cSiO2-induced cytotoxicity compared to OD 1.0 and 2.0. RAW-ASC stimulated with cSiO2 produced robust IL-1β release (272.8 ± 20.9 pg/mL) compared to WT (70.67 ± 9.6 pg/mL). Postbiotics obtained from LGG, REU, and BB12 grown to OD 1.0–3.0 decreased IL-1β release from RAW-ASC. LGG-associated postbiotics from all ODs reduced IL-1β release in WT. However, postbiotics obtained from BB12 at OD 3.0 but not OD 1.0 and 2.0 decreased IL-1β release. Interestingly, only REU postbiotics reduced IL-1α release in RAW-ASC while LGG and BB12 did not alter IL-1α production in both cell lines. Conclusions: Dietary postbiotics can protect against cSiO2-induced cytotoxicity in MΦ. Postbiotics from LGG and BB12 down-regulated release of IL-1β but not IL-1α. We propose that the RAW-ASC cell model is a robust model to study mechanisms by which dietary constituents can activate or suppress inflammasome function. Funding Sources: This work was supported by the USDA National Institute of Food and Federal Appropriations.